Endothelial cell TRPA1 activity exacerbates cerebral hemorrhage during severe hypertension - Sullivan, Michelle N.; Thakore, Pratish; Krishnan, Vivek; Alphonsa, Sushma; Li, Wencheng; Feng Earley, Yumei; Earley, Scott (Frontiers in Molecular Biosciences, 2023)
Hypoxia-induced dilation of cerebral arteries orchestrated by Ca2+-permeable transient receptor potential ankyrin 1 (TRPA1) cation channels on endothelial cells is neuroprotective during ischemic stroke, but it is unknown if the channel has a similar impact during hemorrhagic stroke. TRPA1 channels are endogenously activated by lipid peroxide metabolites generated by reactive oxygen species (ROS). Uncontrolled hypertension, a primary risk factor for hemorrhagic stroke, is associated with increased ROS production and oxidative stress. To test the hypothesis that TRPA1 channel activity is increased during hemorrhagic stroke, severe, chronic hypertension was induced in control (Trpa1fl/fl) and endothelial cell-specific TRPA1 knockout (Trpa1-ecKO) mice using a combination of chronic angiotensin II administration, a high-salt diet, and the addition of a nitric oxide synthase inhibitor to drinking water. All animals became hypertensive, and a majority developed intracerebral hemorrhages or died of unknown causes. Baseline blood pressure and responses to the hypertensive stimulus did not differ between groups. Expression of TRPA1 in cerebral arteries from control mice was not altered after 28 days of treatment, but expression of three NADPH oxidase (NOX) isoforms and the capacity for ROS generation was increased in hypertensive animals. NOX-dependent activation of TRPA1 channels dilated cerebral arteries from hypertensive animals to a greater extent compared with controls. The number of intracerebral hemorrhage lesions in hypertensive animals did not differ between Trpa1fl/fl and Trpa1-ecKO animals, but the lesions were significantly smaller in Trpa1-ecKO mice. However, morbidity and mortality did not differ between groups. We conclude that endothelial cell TRPA1 channel activity increases cerebral blood flow during hypertension resulting in increased extravasation of blood during intracerebral hemorrhage events; however, this effect does not impact overall outcomes.